The Use of Rose Bengal Plate Test to Asses Cattle Exposure to Brucella Infection in Traditional and Smallholder Dairy Production Systems of Tanga Region of Tanzania - Emanuel Senyael Swai; Luuk Schoonman (Veterinary Medicine International)
A cross-sectional epidemiological study was conducted to determine the seroprevalence and to identify risk factors for bovine brucellosis seropositivity in traditional and smallholder dairy cattle production systems in the Tanga region of North-eastern Tanzania. The study populations comprised 246 indigenous and 409 crossbred cattle, randomly selected from 105 smallholder dairy and 25 traditional managed herds, respectively. Individual animal and herd-level data were collected using a structured questionnaire. Serum samples were screened for Brucella antibodies using the Rose Bengal Plate Test The overall seroprevalence of Brucella antibodies in the smallholder dairy and traditional managed cattle was 4.1% and 7.3% respectively. The corresponding overall herd prevalence was 10.5% and 20% respectively. Using multivariate logistic regression analysis, closeness to stock route, access to surface drinking water and location were identified as the major risk factors for individual herd seroprevalence. Older animals (≥6 years) were associated with increased risk of sero-positivity compared to animals of age category of ≤6 years. The results showed that brucellosis is prevalent and widely distributed locally, underscoring the need for further studies including surveillance and institution of preventive and control measures particularly among female young-stock and the general public who are at high risk of contracting brucellosis.